Cynanchum neoleucanthum (Apocynaceae), a replacement name for the later illegitimate homonym Cynanchum leucanthum (K. Schum.) K. Schum - Zhang, Cai-Fei; Onjalalaina, Guy. E.; Liao, Miao; Hu, Guang-Wan (Phytotaxa, 2023)
N/A